Computer simulation of muscle elastic behaviour in drop jumping - Böhm, H.; Senner, V. (International Journal of Computer Science in Sport, 2002)
It is well known that tendon and tendinous tissue of the muscles have elastic properties, which can be determined using ultrasonography (Kubo 2000). From experiments on isolated frog muscles (Kawakami 2000), it is known that shortening of muscle fibres is influenced by the muscle series elasticity. However the exact role in different movements of daily life is still unclear. The purpose of this study is to give insight of the role of muscle series elasticity in drop jumping with the help of computer simulation. Vertical drop jumps from 20 cm are simulated using a two dimensional forward dynamic model. The model consists of 4 rigid bodies and 8 functional grouped one and two joint Hill-type muscles around hip, knee and ankle joints. The active state of the muscle was modeled with sinusoidal functions. These functions were optimized, so that the body center of mass reached maximum jump height. Drop jumps from different heights with different ground contact times from were simulated and compared to experimental data (Arampatzisl999) to validate the model. Three hypotheses about the effect of series elasticity on jumping performance were tested. First if a considerable amount of series elastic energy can be stored and is released afterwards. Second if the contractile elements (CE) can work at their optimal velocity and third if the CE can work in their optimal length. The model showed the same behavior as the drop jump measured. Therefore it is valid to discuss the mechanical energy processes in the contractile and series elastic elements of the muscle. A considerable amount of energy 30 percent of the body positive jumping energy was stored in all muscles series elastic elements (SEE). The velocity of the CE in concentric was lower than that of the muscle tendon unit so that due to the force velocity relation a higher force can be generated. With the help of the SEE some muscles are able to function at their optimal length, but this was not true for all muscles in the model.